2017
DOI: 10.1128/aac.01048-16
|View full text |Cite
|
Sign up to set email alerts
|

Multiclonal Expansion of Klebsiella pneumoniae Isolates Producing NDM-1 in Rio de Janeiro, Brazil

Abstract: We characterized NDM-1-producing isolates from Rio de Janeiro, Brazil. PCR was applied for resistance and virulence determinants. The genetic context of was determined by S1 nuclease pulsed-field gel electrophoresis (PFGE) and hybridization. Genotyping was performed by PFGE and multilocus sequence typing (MLST). Most isolates carried multiple resistance genes and remained susceptible to amikacin, fosfomycin-trometamol, polymyxin B, and tigecycline. The spread of NDM-1-producing was not associated with clonal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
2
19
1
2
Order By: Relevance
“…The high percentage (73%) of resistance to colistin found differs from that described in other geographical areas of the world (Guzmán-Blanco et al, 2014 ; Pereira et al, 2015 ; Aires et al, 2017 ). As such the presence of mcr-1 and mcr-2 was assessed by PCR, using primers listed in Tables S2 , since these genes were described as the first transferable mechanism of colistin resistance (Liu et al, 2016 ); none of the isolates was found to carry them.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The high percentage (73%) of resistance to colistin found differs from that described in other geographical areas of the world (Guzmán-Blanco et al, 2014 ; Pereira et al, 2015 ; Aires et al, 2017 ). As such the presence of mcr-1 and mcr-2 was assessed by PCR, using primers listed in Tables S2 , since these genes were described as the first transferable mechanism of colistin resistance (Liu et al, 2016 ); none of the isolates was found to carry them.…”
Section: Discussioncontrasting
confidence: 64%
“…The pulse types of these two strains have a genetic identity < 85% with respect to the KPC producing strains, as shown in Figure 1 . Also, their STs have only been previously described in Brazil, in strains producing the same carbapenemases; furthermore the OXA-370 variant had been only reported previously in Brazil (Pereira et al, 2015 ; Aires et al, 2017 ). This leads us to hypothesize that both isolates could represent cases imported from Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…346 kb, acc.no. MDCA00000000)[22]. Moreover, this last plasmid did not contain rmtC and harboured bla NDM-1 associated with Tn 3000 [17].…”
Section: Resultsmentioning
confidence: 99%
“…Observou-se que a bactéria K. pneumoniae KPC não apresentou grande variação dos halos, sendo 4 mm observado na concentração de 0,25% e 6 mm na máxima concentração testada. Sugere-se que a morfologia das colônias produzidas pelo gênero Klebsiella, com seu aspecto mucoide, pode ser um fator prejudicial na visualização de halos de inibição e a hipótese levantada é conirmada por Aires et al (2017).…”
Section: Resultsunclassified